2017
DOI: 10.1016/j.eatbeh.2016.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and promoting treatment-seeking for eating disorders and body image concerns on college campuses through online screening, prevention and intervention

Abstract: While there have been important recent advances in the development of effective universal prevention and intervention programs, it is not yet clear how to engage large numbers of students in these programs. In this paper, we report findings from a two-phase pilot study. In the first phase, we used a population-level, online survey to assess eating disorder symptom level and habits/attitudes related to service utilization (N=2,180). Using validated screening tools, we found that roughly one in three students ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
56
4
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(76 citation statements)
references
References 21 publications
7
56
4
1
Order By: Relevance
“…This qualitative finding is consistent with prior studies about barriers to ED treatment (Ali et al, 2017;Eisenberg, Nicklett, Roeder, & Kirz, 2011;Lipson et al, 2017). This qualitative finding is consistent with prior studies about barriers to ED treatment (Ali et al, 2017;Eisenberg, Nicklett, Roeder, & Kirz, 2011;Lipson et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This qualitative finding is consistent with prior studies about barriers to ED treatment (Ali et al, 2017;Eisenberg, Nicklett, Roeder, & Kirz, 2011;Lipson et al, 2017). This qualitative finding is consistent with prior studies about barriers to ED treatment (Ali et al, 2017;Eisenberg, Nicklett, Roeder, & Kirz, 2011;Lipson et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…Most participants did not arrange for ED treatment prior to beginning university because they did not think they would need it, overall underestimating disease severity. This qualitative finding is consistent with prior studies about barriers to ED treatment (Ali et al, 2017;Eisenberg, Nicklett, Roeder, & Kirz, 2011;Lipson et al, 2017). Treatment for EDs in adolescents, especially for AN, is traditionally family-focused and initiated by parents, and the loss of "monitoring" has been cited as a common reason for relapses during the transition to adult care (Dimitropoulos et al, 2015).…”
Section: Discussionsupporting
confidence: 87%
“…This study identi ed several implications of exclusionary ED discourse and resultant shame and embarrassment for help-seeking. Consistent with previous ndings, this study indicated that many emerging adults have a preference for self-su ciency, with many deciding to deal with their di culties alone (15,(24)(25)(26)(27)35). This study identi ed that many emerging adults use self-help resources as a rst port of call.…”
Section: Phase 3: Feeling Excluded From Eating Disorder Discoursesupporting
confidence: 88%
“…However, scarce research has focused speci cally on reasons for delayed ED helpseeking during transition to adulthood. Some studies have examined ED help-seeking in university students, and have found that low perceived need, practical considerations and preference for selfsu ciency are important barriers in university student populations, yet such ndings cannot be easily extrapolated to non-university attending young people (15,28,29).…”
mentioning
confidence: 99%
“…Indeed, even in healthcare systems with limited and constrained resources [like that of the United States (US)], there is cost‐offset to addressing mental health issues (Chiles, Lambert, & Hatch, ; Gabbard, Lazar, Hornberger, & Spiegel, ; Levant, House, May, & Smith, ). Although health services are commonly available on US college campuses, the process by which students seek care to address mental health problems is fraught with barriers (Czyz, Horwitz, Eisenberg, Kramer, & King, ; Eisenberg, Hunt, & Speer, ; Lipson et al, ; Mowbray et al, ), as shown in Figure . Many students do not present to or receive care (Eisenberg et al, ; Eisenberg, Hunt, Speer, & Zivin, ; National Research Council, ) given these barriers, which can delay treatment and lead to poorer prognosis and greater relapse rates (American Psychiatric Association, ).…”
Section: Introductionmentioning
confidence: 99%